Cognitive-behavioural therapy does not meaningfully reduce depression in most people with epilepsy: a systematic review of clinically reliable improvement. Issue 11 (7th May 2018) - Noble, Adam J; Reilly, James; Temple, James; Fisher, Peter L
Abstract : Psychological treatment is recommended for depression and anxiety in those with epilepsy. This review used standardised criteria to evaluate, for the first time, the clinical relevance of any symptom change these treatments afford patients. Databases were searched until March 2017 for relevant trials in adults. Trial quality was assessed and trial authors asked for individual participants' pre-treatment and post-treatment distress data. Jacobson's methodology determined the proportion in the different trial arms demonstrating reliable symptom change on primary and secondary outcome measures and its direction. Search yielded 580 unique articles; only eight eligible trials were identified. Individual participant data for five trials—which included 398 (85%) of the 470 participants randomised by the trials—were received. The treatments evaluated lasted 7 hours and all incorporated cognitive-behavioural therapy (CBT). Depression was the primary outcome in all; anxiety a secondary outcome in one. On average, post-treatment assessments occurred 12 weeks following randomisation; 2 weeks after treatment had finished. There were some limitations in how trials were conducted, but overall trial quality was 'good'. Pooled risk difference indicated likelihood of reliable improvement in depression symptoms was significantly higher for those randomised to CBT. The extent of gain was though low—the depressive symptoms of most participants (66.9%) receiving CBT were 'unchanged' and 2.7% 'reliably deteriorated'. Only 30.4% made a 'reliable improvement. This compares with 10.2% of participants in the control arms who 'reliably improved' without intervention. The effect of the treatments on secondary outcome measures, including anxiety, was also low. Existing CBT treatments appear to have limited benefit for depression symptoms in epilepsy. Almost 70% of people with epilepsy do not reliably improve following CBT. Only a limited number of trials have though been conducted in this area and there remains a need for large, well-conducted trials.